Perovskite-type lithium adsorbent, preparation method and application thereof
Through the preparation method of perovskite lithium adsorbent, combined with sol-gel method and high-temperature sintering technology, the existing lithium adsorbent cannot take into account multiple performance problems, and achieve efficient and stable lithium adsorption and lithium extraction effects.
Patent Information
- Application Number
- CN202410403570.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-04-03
AI Technical Summary
Existing lithium adsorbents cannot take into account the problems of strong selectivity, large adsorption capacity, long cycle life, easy molding and processing, and the application of multiple types of salt lake brine.
The perovskite lithium adsorbent is prepared by sol-gel method combined with high-temperature sintering to form a LixLayTiO3 precursor, and then acid-eluting lithium is performed to obtain the perovskite lithium adsorbent HxLayTiO3, and molded by high-temperature sintering.
It has achieved stable properties of lithium adsorbent, low acid leaching loss, long cycle life, large lithium adsorption capacity and high lithium selectivity, and is suitable for the adsorption method of various salt lake brines.
Smart Images

Figure CN118267965B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium adsorbents, and in particular to a perovskite-type lithium adsorbent, a preparation method thereof and applications thereof. Background Art
[0002] Lithium is known as the "energy metal of the 21st century". With the rapid development of electronic products and new energy vehicles, the global demand for lithium has shown explosive growth, and traditional ore lithium resources can no longer meet the growing demand. Salt lake-type lithium resources account for nearly 60% of the world's total proven lithium resources, and various types of brine lithium account for nearly 80% of China's total lithium resources. The cost of extracting lithium from salt lake brine is relatively low, and industrial-grade lithium carbonate can be directly obtained, which can be converted into deep-processed lithium products after purification. Therefore, salt lake lithium extraction technology is very critical to the vigorous development of my country's lithium resources. At present, my country's salt lake lithium extraction mainly adopts adsorption, solvent extraction, membrane separation, calcination leaching, solar pond and electrochemical methods. Among them, the adsorption method can achieve low-cost lithium extraction from low-grade salt lakes, and has become the main technical route used in the current construction of salt lake lithium extraction capacity.
[0003] The adsorption method mainly uses selective adsorbents to adsorb Li + , and then use the eluent to remove Li + After elution, the nanofiltration membrane is used to remove magnesium under acidic conditions, and high-lithium qualified liquid is obtained after reverse osmosis concentration and natural evaporation concentration in the salt field. Finally, lithium carbonate products are obtained by precipitation and filtration. At present, the commonly used adsorbents for lithium extraction from salt lakes mainly include aluminum molecular sieve adsorbents, manganese ion sieve adsorbents and titanium ion sieve adsorbents.
[0004] Among them, aluminum molecular sieves are suitable for widely distributed chloride salt lakes and magnesium sulfate subtype salt lakes. They only need to be analyzed with fresh water and the adsorption analysis time is short; but in alkaline salt lakes rich in hydroxide, aluminum adsorbents cannot be used directly. The advantages of manganese ion sieves are good adsorption capacity, good selectivity and stability for lithium ions; but manganese has serious dissolution problems during acid analysis, and the adsorption capacity tends to decrease with time. Titanium ion sieves have stable properties, low dissolution, good acid resistance, and large adsorption capacity; but the permeability and adsorption rate are low, and the adsorption cycle is long. In addition, the adsorbent will have problems such as reduced capacity after granulation, which limits its performance in practical applications. Therefore, the development of a moldable adsorbent with strong selectivity, large adsorption capacity, long cycle life, and a wide range of applicable salt lake brine types is a key issue in lithium extraction by adsorption. Summary of the invention
[0005] The main purpose of the present invention is to provide a perovskite-type lithium adsorbent, a preparation method and application thereof, so as to solve the problem that the lithium adsorbent in the prior art cannot have strong selectivity, large adsorption capacity, long cycle life, simple molding and processing, and applicability to various types of salt lake brine.
[0006] In order to achieve the above object, according to one aspect of the present invention, a method for preparing a perovskite-type lithium adsorbent is provided, wherein the chemical formula of the perovskite-type lithium adsorbent is H x La y TiO 3 , x is 0.05 to 1.85, y is 0.05 to 0.65, and x+3y=2 is satisfied; the preparation method comprises the following steps: step S1, mixing a lithium source, a lanthanum source, a titanium source and a complexing agent, heating and drying them in sequence to obtain a precursor gel; step S2, oxidizing and sintering the precursor gel to obtain a precursor oxide; step S3, shaping and sintering the precursor oxide to obtain Li x La y TiO 3 molding material; step S4, Li x La y TiO 3 The molding material is acid-leached to obtain a perovskite-type lithium adsorbent; wherein the temperature of oxidation sintering is 500-1200°C, and the temperature of molding sintering is 950-1350°C.
[0007] Furthermore, in step S2, the oxidative sintering includes a first sintering and a second sintering performed sequentially, the temperature of the second sintering is higher than the first sintering, and the temperature difference is 450-550°C; preferably, the temperature of the first sintering is 500-700°C, and the time is 3-5h; the temperature of the second sintering is 1000-1200°C, and the time is 18-22h.
[0008] Furthermore, in step S3, the molding sintering includes a third sintering and a fourth sintering performed sequentially, the temperature of the fourth sintering is higher than the third sintering, and the temperature difference is 200-250°C; preferably, the temperature of the third sintering is 950-1150°C, and the time is 3-5h; the temperature of the fourth sintering is 1150-1350°C, and the time is 6-10h.
[0009] Furthermore, the heating rates of oxidation sintering and molding sintering are independently 0.2-8°C / min; preferably, before molding sintering, step S3 also includes the step of ball milling the precursor oxide; more preferably, the ball milling speed is 450-550rpm, and the time is 10-14h.
[0010] Further, in step S1, the molar ratio of the lithium source, the lanthanum source and the titanium source is (5-200):(5-65):100; and / or the molar ratio of the titanium source and the complexing agent is 1:(20-150); preferably, the lithium source includes one or more of lithium nitrate, lithium carbonate and lithium chloride; and / or the lanthanum source includes one or more of lanthanum nitrate, lanthanum trioxide and lanthanum trichloride; and / or the titanium source includes one or more of titanium tert-butoxide, tetrabutyl titanate and titanium dioxide; and / or the complexing agent includes one or more of citric acid, fruit acid and citric acid; and / or the heating temperature is 60-120°C, and the drying temperature is 130-180°C.
[0011] Further, in step S4, the molar concentration of the acid used for acid leaching is 0.5-1.5 mol / L, and the acid leaching time is 25-35 min; and / or the acid includes an inorganic acid and / or an organic acid; preferably, the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid.
[0012] According to another aspect of the present invention, a perovskite-type lithium adsorbent is provided, which is obtained by the above-mentioned preparation method of the present invention.
[0013] According to another aspect of the present invention, a method for extracting lithium is provided, wherein the perovskite-type lithium adsorbent of the present invention is used as an adsorbent to extract lithium.
[0014] Furthermore, the lithium extraction method comprises the following steps: taking brine, adding a perovskite-type lithium adsorbent for a first soaking, filtering, obtaining an adsorption mother solution and a loaded Li + Adsorbent; take loaded Li + The adsorbent is soaked in acid for a second time, filtered, and a lithium-containing desorption solution and a reused perovskite-type lithium adsorbent are obtained.
[0015] Furthermore, the mass concentration of ions in brine is: Na + 10~100g / L, K + 2~50g / L, Mg 2+ 0.1~50g / L, Ca 2+ 0.1~2g / L, Li + 0.01~1g / L, B 3+ 0.01~1g / L, SO 4 2- 1~10g / L, Cl -20-200 g / L, the mass ratio of Mg to Li is (0.1-5000):1; and / or the liquid-solid ratio of brine to perovskite lithium adsorbent is 1000 mL:(0.8-1.2 g); and / or the time for the first immersion and the second immersion is 50-70 min; and / or the molar concentration of the acid is 0.3-0.8 mol / L, and the acid includes an inorganic acid and / or an organic acid; preferably, the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid.
[0016] The technical solution of the present invention is applied to synthesize Li by sol-gel method combined with high temperature sintering. x La y TiO 3 Precursor, and then acid elution to remove lithium to obtain perovskite lithium adsorbent H x La y TiO 3 The lithium adsorbent is formed by high-temperature sintering, which avoids the loss of adsorbent capacity caused by traditional granulation. The perovskite-type salt lake lithium adsorbent of the present invention has stable properties, low acid leaching loss, long cycle life, and high lithium adsorption capacity and lithium selectivity, and is suitable for lithium extraction from a variety of salt lake brines by adsorption. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0018] Figure 1 A bar graph showing the lithium adsorption capacity according to Examples 1 to 3 of the present invention is shown;
[0019] Figure 2 A bar graph showing the lithium adsorption capacity retention rate after 5 cycles according to Examples 1 to 3 of the present invention; and
[0020] Figure 3 The magnesium-lithium ratio in the desorption solution according to Examples 1 to 3 of the present invention is shown. DETAILED DESCRIPTION
[0021] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0022] As described in the background of the present invention, the prior art has the problem that lithium adsorbents cannot take into account strong selectivity, large adsorption capacity, long cycle life, simple molding and processing, and applicability to a variety of salt lake brine types. In order to solve the above problems, in a typical embodiment of the present invention, a method for preparing a perovskite-type lithium adsorbent is provided. The chemical formula of the perovskite-type lithium adsorbent is H x La y TiO 3 , x is 0.05 to 1.85, y is 0.05 to 0.65, and x+3y=2 is satisfied; the preparation method comprises the following steps: step S1, mixing a lithium source, a lanthanum source, a titanium source and a complexing agent, heating and drying them in sequence to obtain a precursor gel; step S2, oxidizing and sintering the precursor gel to obtain a precursor oxide; step S3, shaping and sintering the precursor oxide to obtain Li x La y TiO 3 molding material; step S4, Li x La y TiO 3 The molding material is acid-leached to obtain a perovskite-type lithium adsorbent; wherein the first sintering temperature is 500-1200°C, and the second sintering temperature is 950-1350°C.
[0023] Specifically, the present invention first prepares Li by a sol-gel method. x La y TiO 3 . The lithium source and lanthanum source are dissolved in the complexing agent aqueous solution, and the titanium source is added under vigorous stirring, and the reaction mixture is heated to mix and form a sol; the heating is continued until the solution is completely dry to obtain a precursor gel. Secondly, the precursor gel is oxidized and sintered in an air atmosphere or an oxygen atmosphere, and the precursor gel is burned under the action of oxygen to obtain a precursor oxide Li x La y TiO 3 The precursor oxide is then formed and sintered to fuse the precursor oxide powders (particles) to obtain Li x La y TiO 3 The molding material is formed by high-temperature sintering, which can avoid the loss of adsorbent capacity caused by insufficient contact between the adsorbent and the solution due to the molding agent coating the adsorbent surface in traditional granulation molding. Under the above temperature conditions, the prepared adsorbent can have stable properties, low acid leaching loss, and long cycle life. The prepared adsorbent can be recycled 2 to 10 times. x La y TiO 3 The molding material is pickled, H + Lix La y TiO 3 Li + Replace it and get H x La y TiO 3 The hydrogen-type adsorbent is the perovskite-type lithium adsorbent of the present invention.
[0024] The present invention defines the chemical formula of the perovskite lithium adsorbent as H x La y TiO 3 , x is 0.05-1.85, y is 0.05-0.65, and x+3y=2 is satisfied, because the inventor unexpectedly found during the research that too low x will lead to a smaller adsorption capacity, and too high x will lead to a lower selectivity. Under the above ratio, the crystal structure of the adsorbent is more conducive to lithium ion transmission, and the adsorption rate and selectivity are higher, which is suitable for lithium extraction by adsorption from a variety of salt lake brines. The y value is further used to balance the valence. Among them, the precursor oxide Li x La y TiO 3 Other conventional methods in the art may also be used for preparation, such as a solid phase reaction method or a hydrothermal method, which are understandable to those skilled in the art and will not be described in detail here.
[0025] In a preferred embodiment, in step S2, the oxidation sintering includes a first sintering and a second sintering performed sequentially, the temperature of the second sintering is higher than the first sintering, and the temperature difference is 450-550°C. By pre-sintering at a low temperature to remove organic matter, it is possible to avoid the generation of by-products by a high-temperature sintering, which affects the purity of the oxide. Preferably, the temperature of the first sintering is 500-700°C, and the time is 3-5h; the temperature of the second sintering is 1000-1200°C, and the time is 18-22h. The above two-stage sintering and the specific sintering temperature and sintering time can better control the adsorbent particle size. The higher the temperature or the longer the time, the larger the particle size. Under the above conditions, the particle size of the oxide can be made more uniform and suitable, and has a higher purity to facilitate subsequent molding and sintering.
[0026] In order to further extend the cycle life of the adsorbent, in a preferred embodiment, in step S3, the molding sintering includes the third sintering and the fourth sintering performed in sequence, the temperature of the fourth sintering is higher than the third sintering, the temperature difference is 200-250°C, and the pre-sintering at low temperature and then the temperature is increased to sinter, which can improve the degree of fusion between the precursor oxide powders and further enhance the molding effect. Preferably, the temperature of the third sintering is 950-1150°C, and the time is 3-5h; the temperature of the fourth sintering is 1150-1350°C, and the time is 6-10h. When the temperature is low or the time is short, it is easy to make the degree of fusion between the oxide powders insufficient, resulting in difficulty in molding the adsorbent; when the temperature is high or the time is long, it is easy to cause serious volatilization of lithium elements in the oxide, affecting the internal structure of the adsorbent. Therefore, the preferred molding sintering temperature and time of the present invention are within the above range, which can make the oxide more smoothly molded while the internal structure is complete, the adsorbent has stable properties, and the acid leaching loss is lower.
[0027] In a preferred embodiment, the heating rates of oxidation sintering and molding sintering are independently 0.2-8°C / min, which is more suitable for the temperature environment of the above-mentioned oxidation sintering and molding sintering of the present invention; preferably, before molding sintering, step S3 also includes the step of ball milling the precursor oxide; more preferably, the ball milling speed is 450-550rpm, and the time is 10-14h, so that the oxide particles or powder can be made more uniform and fine, which is beneficial to the mutual fusion of the oxide particles or powders during the molding sintering process, further improving the molding effect, and improving the cycle life, adsorption rate and selectivity of the adsorbent.
[0028] For the purpose of being more suitable for the actual preparation of the adsorbent and further reducing the cost, in a preferred embodiment, in step S1, the molar ratio of the lithium source, the lanthanum source and the titanium source is (5-200): (5-65): 100; and / or the molar ratio of the titanium source and the complexing agent is 1: (20-150); and / or the lithium source includes one or more of lithium nitrate, lithium carbonate and lithium chloride; and / or the lanthanum source includes one or more of lanthanum nitrate, lanthanum trioxide and lanthanum trichloride; and / or the titanium source includes one or more of titanium tert-butylate, tetrabutyl titanate and titanium dioxide; and / or the complexing agent includes one or more of citric acid, fruit acid and citric acid; and / or the heating temperature is 60-120° C., and the drying temperature is 130-180° C., which is more convenient for the Li ionization process of the present invention to be carried out by the sol-gel method. x La y TiO 3 preparation.
[0029] In a preferred embodiment, in step S4, the molar concentration of the acid used for acid leaching is 0.5-1.5 mol / L, and the acid leaching time is 25-35 min. Too low a molar concentration or too short an acid leaching time is likely to lead to reduced replacement efficiency, and too high a molar concentration or too long an acid leaching time is likely to increase operating costs; and / or the acid includes an inorganic acid and / or an organic acid; preferably, the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid, which is more suitable for the present invention. x La y TiO 3 Middle + Replacement.
[0030] In another typical embodiment of the present invention, a perovskite-type lithium adsorbent is provided, which is obtained by the above-mentioned preparation method of the present invention. It has stable properties, low acid leaching loss, long cycle life, and high lithium adsorption capacity and lithium selectivity, and is suitable for lithium extraction by adsorption from a variety of salt lake brines.
[0031] In another typical embodiment of the present invention, a lithium extraction method is also provided, which uses the above-mentioned perovskite-type lithium adsorbent of the present invention as an adsorbent to extract lithium, and has high lithium extraction efficiency and good lithium extraction effect.
[0032] In a preferred embodiment, the lithium extraction method comprises the following steps: taking brine, adding a perovskite-type lithium adsorbent for a first soaking, filtering, obtaining an adsorption mother solution and a loaded Li + Adsorbent; take loaded Li + The adsorbent is soaked in acid for a second time and filtered to obtain a lithium-containing desorption solution and a reused perovskite-type lithium adsorbent, wherein the adsorption mother liquor can be used as a brine raw material and repeatedly adsorbed by the adsorbent. After the lithium-containing desorption solution is collected, sodium carbonate is added to obtain lithium carbonate through precipitation.
[0033] After lithium adsorption and desorption, the perovskite-type lithium adsorbent with high lithium adsorption capacity and lithium selectivity of the present invention can fully extract lithium from salt lake brine, and due to its stable properties and low acid leaching loss, the adsorbent can be recycled 2 to 10 times, which is more convenient for practical application and can reduce the cost of lithium extraction. The Mg / Li ratio (magnesium-lithium ratio) in the lithium-containing analytical solution can reflect the selectivity of Li. When the initial solutions are the same, the magnesium-lithium ratio in the analytical solution is relatively low, indicating that the lithium selectivity of the adsorption material is good.
[0034] Specifically, in a preferred embodiment, the mass concentration of ions in the brine is: Na + 10~100g / L, K + 2~50g / L, Mg 2+ 0.1~50g / L, Ca 2+0.1~2g / L, Li + 0.01~1g / L, B 3+ 0.01~1g / L, SO 4 2- 1~10g / L, Cl - 20~200g / L, the mass ratio of Mg to Li is (0.1~5000):1; preferably Na + 78~80g / L, K + 8~10g / L, Mg 2+ 14.7~19g / L, Ca 2+ 0.5~0.9g / L, Li + 0.1~0.2g / L, B 3+ 0.1~0.3g / L, SO 4 2- 5~7g / L, Cl - 185-200 g / L, the mass ratio of Mg to Li is (95-98):1, which is more suitable for using the adsorbent of the present invention for lithium extraction, and can broaden the applicable salt lake brine types; and / or the liquid-solid ratio of brine to perovskite lithium adsorbent is 1000 mL:(0.8-1.2 g); and / or the time for the first immersion and the second immersion is 50-70 min; and / or the molar concentration of the acid is 0.3-0.8 mol / L, and the acid includes an inorganic acid and / or an organic acid; preferably, the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid. Under the above conditions, the efficiency of lithium adsorption and desorption is higher, and the lithium extraction effect is better.
[0035] Typically, but not exclusively, the chemical formula of the perovskite-type lithium adsorbent is H x La y TiO 3 , x is 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65, 0.70, 0.75, 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, 1.35, 1.40, 1.4 5, 1.50, 1.55, 1.60, 1.65, 1.70, 1.75, 1.80, 1.85 or any two of them, y is 0.05, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, 0.55, 0.60, 0.65 or any two of them, and x+3y=2.
[0036] Typically but not limiting, in step S1, the molar ratio of the titanium source to the complexing agent is 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140, 1:150 or a boundary value consisting of any two of them; the heating temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C or a boundary value consisting of any two of them; the drying temperature is 130°C, 140°C, 150°C, 160°C, 170°C, 180°C or a boundary value consisting of any two of them.
[0037] Typically but not limiting, in step S2, the temperature of the oxidation sintering is 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C or a boundary value consisting of any two of them.
[0038] Typically but not limiting, in step S2, the oxidative sintering includes a first sintering and a second sintering performed sequentially, the temperature of the second sintering is higher than the first sintering, and the temperature difference is 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C or a boundary value composed of any two of them.
[0039] Typically but not limitatively, in step S2, the oxidation sintering includes a first sintering and a second sintering performed sequentially, the temperature of the first sintering is 500°C, 520°C, 540°C, 550°C, 560°C, 580°C, 600°C, 620°C, 640°C, 650°C, 660°C, 680°C, 700°C or a boundary value composed of any two of them, and the time is 3h, 3.5h, 4h, 4.5h, 5h or a boundary value composed of any two of them; The temperature of the second sintering is 1000°C, 1020°C, 1040°C, 1050°C, 1060°C, 1080°C, 1100°C, 1120°C, 1140°C, 1150°C, 1160°C, 1180°C, 1200°C or a boundary value composed of any two of their numerical values, and the time is 18h, 18.5h, 19h, 19.5h, 20h, 20.5h, 21h, 21.5h, 22h or a boundary value composed of any two of their numerical values.
[0040] Typically but not limiting, in step S3, the molding and sintering temperature is 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1350°C or a boundary value consisting of any two of them.
[0041] Typically but not limiting, in step S3, the molding sintering includes a third sintering and a fourth sintering performed sequentially, the temperature of the fourth sintering is higher than the temperature of the third sintering, and the temperature difference is 200°C, 210°C, 220°C, 230°C, 240°C, 250°C or a boundary value composed of any two of them.
[0042] Typically but not limiting, in step S3, the molding sintering includes a third sintering and a fourth sintering performed in sequence, the temperature of the third sintering is 950°C, 960°C, 980°C, 1000°C, 1020°C, 1050°C, 1060°C, 1080°C, 1100°C, 1120°C, 1140°C, 1150°C or a boundary value composed of any two of them, and the time is 3h, 3.5h, 4h, 4.5h, 5h or a boundary value composed of any two of them. the fourth sintering temperature is 1150℃, 1160℃, 1180℃, 1200℃, 1220℃, 1240℃, 1250℃, 1260℃, 1280℃, 1300℃, 1320℃, 1340℃, 1350℃ or the boundary values composed of any two of them, and the time is 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h or the boundary values composed of any two of them.
[0043] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0044] Example 1: H 0.29 La 0.57 TiO 3 Preparation of adsorbent
[0045] Step S1, 33 parts of LiNO 3 and 57 parts of La(NO 3 ) 3 Dissolve in an aqueous solution containing 6500 parts of citric acid, add 100 parts of titanium (IV) tert-butylate under vigorous stirring, heat to 80°C to obtain a uniform solution, and continue to heat to 150°C until the solution is completely dry to obtain a solid;
[0046] Step S2, sintering the obtained solid at 600°C for 4 hours, and then heating to 1100°C at a rate of 5°C / min and sintering for 20 hours to obtain white Li 0.29 La 0.57 TiO 3 The powder is the precursor oxide.
[0047] Step S3, the obtained white powder was ball-milled at 500 rpm for 12 hours, placed in a tungsten carbide particle mold and pressed into a cylindrical shape with a diameter of 50 mm and a thickness of 70 mm; first sintered at 1050°C for 4 hours, then heated to 1275°C at a rate of 5°C / min and sintered for 8 hours to obtain Li 0.29 La 0.57 TiO 3 Molding material.
[0048] Step S4, the obtained Li 0.29 La 0.57 TiO 3 The molding material was immersed in 1 mol / L HCl solution and stirred for 30 min to obtain H 0.29 La 0.57 TiO 3 The hydrogen-type adsorbent is the perovskite-type lithium adsorbent of the present invention.
[0049] Take 1000 mL of brine, the composition of which is shown in Table 1, adjust the pH to 8.0 with 0.1 mol / L NaOH solution, add 1 g of the prepared hydrogen-type adsorbent, soak for 60 min under stirring, filter, and obtain the adsorption mother solution L 1 , determine its Li + Mg 2+ Content, get filter cake S 1 That is the load Li + Adsorbent; when loaded with Li + Adsorbent S 1 Add 150 mL of 0.5 mol / L hydrochloric acid, soak for 60 min under stirring, filter, and obtain lithium-containing desorption solution L 2 , determine its Li + Mg 2+ The content of filter cake S 2 That is, the perovskite type lithium adsorbent is reused, and the perovskite type lithium adsorbent can be recycled.
[0050] Example 2: H 0.44 La 0.52 TiO 3 Preparation of adsorbent
[0051] The difference from Example 1 is that in step S1, 49 parts of LiNO 3 and 52 parts of La(NO 3 ) 3 Dissolve in an aqueous solution containing 6500 parts of citric acid, add 100 parts of titanium (IV) tert-butoxide under vigorous stirring, heat to 80°C to obtain a uniform solution, and continue to heat to 150°C until the solution is completely dry to obtain a solid.
[0052] Example 3: H 0.29 La0.57 TiO 3 Preparation of adsorbent
[0053] The difference from Example 1 is that in step S1, 33 parts of LiNO 3 and 57 parts of La(NO 3 ) 3 Dissolve in an aqueous solution containing 6500 parts of citric acid, add 100 parts of rutile TiO 2 , heated to 80°C to obtain a uniform solution, and continued to heat to 150°C until the solution was completely dried to obtain a solid.
[0054] Example 4: H 0.05 La 0.65 TiO 3 Preparation of adsorbent
[0055] The difference from Example 1 is that in step S1, 6 parts of lithium carbonate and 32.5 parts of lanthanum trioxide are dissolved in an aqueous solution containing 15,000 parts of fruit acid, 100 parts of tetrabutyl titanate are added under vigorous stirring, the solution is heated to 60° C. to obtain a uniform solution, and the solution is further heated to 130° C. until the solution is completely dry to obtain a solid.
[0056] Example 5: H 1.85 La 0.05 TiO 3 Preparation of adsorbent
[0057] The difference from Example 1 is that in step S1, 200 parts of lithium chloride and 5 parts of lanthanum trichloride are dissolved in an aqueous solution containing 2000 parts of citric acid, 100 parts of titanium dioxide are added under vigorous stirring, and the mixture is heated to 120° C. to obtain a uniform solution, and the mixture is further heated to 180° C. until the solution is completely dried to obtain a solid.
[0058] Example 6
[0059] The difference from Example 1 is that in step S2, the obtained solid is sintered at 600°C for 4 hours, and then heated to 1050°C at a rate of 5°C / min and sintered for 20 hours to obtain white Li 0.29 La 0.57 TiO 3 The powder is the precursor oxide.
[0060] Example 7
[0061] The difference from Example 1 is that in step S2, the obtained solid is sintered at 600°C for 4 hours, and then the temperature is raised to 1150°C at a rate of 5°C / min and sintered for 20 hours to obtain white Li 0.29 La 0.57 TiO 3 The powder is the precursor oxide.
[0062] Example 8
[0063] The difference from Example 1 is that in step S2, the obtained solid is sintered at 500°C for 5 hours, and then heated to 1000°C at a rate of 0.2°C / min and sintered for 22 hours to obtain white Li 0.29 La 0.57 TiO 3 The powder is the precursor oxide.
[0064] Example 9
[0065] The difference from Example 1 is that in step S2, the obtained solid is sintered at 700°C for 3 hours, and then heated to 1200°C at a rate of 8°C / min and sintered for 18 hours to obtain white Li 0.29 La 0.57 TiO 3 The powder is the precursor oxide.
[0066] Example 10
[0067] The difference from Example 1 is that in step S3, the obtained white powder is ball-milled at 500 rpm for 12 hours, placed in a tungsten carbide particle mold and pressed into a cylindrical shape with a diameter of 50 mm and a thickness of 70 mm; first sintered at 1050°C for 4 hours, then heated to 1250°C at a rate of 5°C / min and sintered for 8 hours to obtain Li 0.29 La 0.57 TiO 3 Molding material.
[0068] Embodiment 11
[0069] The difference from Example 1 is that in step S3, the obtained white powder is ball-milled at 500 rpm for 12 hours, placed in a tungsten carbide particle mold and pressed into a cylindrical shape with a diameter of 50 mm and a thickness of 70 mm; first sintered at 1050°C for 4 hours, then heated to 1300°C at a rate of 5°C / min and sintered for 8 hours to obtain Li 0.29 La 0.57 TiO 3 Molding material.
[0070] Example 12
[0071] The difference from Example 1 is that in step S3, the obtained white powder is ball-milled at 450 rpm for 14 hours, placed in a tungsten carbide particle mold and pressed into a cylindrical shape with a diameter of 50 mm and a thickness of 70 mm; first sintered at 950°C for 5 hours, then heated to 1150°C at a rate of 0.2°C / min and sintered for 10 hours to obtain Li 0.29 La 0.57TiO 3 Molding material.
[0072] Example 13
[0073] The difference from Example 1 is that in step S3, the obtained white powder is ball-milled at 550 rpm for 10 hours, placed in a tungsten carbide particle mold and pressed into a cylindrical shape with a diameter of 50 mm and a thickness of 70 mm; first sintered at 1150°C for 3 hours, then heated to 1350°C at a rate of 8°C / min and sintered for 6 hours to obtain Li 0.29 La 0.57 TiO 3 Molding material.
[0074] Embodiment 14
[0075] The difference from Example 1 is that in step S4, the obtained Li 0.29 La 0.57 TiO 3 The molding material was immersed in a 0.5 mol / L sulfuric acid solution and stirred for 25 min to obtain H 0.29 La 0.57 TiO 3 The hydrogen-type adsorbent is the perovskite-type lithium adsorbent of the present invention.
[0076] Embodiment 15
[0077] The difference from Example 1 is that in step S4, the obtained Li 0.29 La 0.57 TiO 3 The molding material was immersed in 1.5 mol / L acetic acid solution and stirred for 35 min to obtain H 0.29 La 0.57 TiO 3 The hydrogen-type adsorbent is the perovskite-type lithium adsorbent of the present invention.
[0078] Example 16
[0079] The difference from Example 1 is that 1000 mL of brine with the composition shown in Table 1 was taken, the pH was adjusted to 8.0 with 0.1 mol / L NaOH solution, 0.8 g of the prepared hydrogen-type adsorbent was added, and the mixture was stirred and soaked for 70 min, and filtered to obtain the adsorption mother solution L 1 , determine its Li + Mg 2+ Content, get filter cake S 1 That is the load Li + Adsorbent; when loaded with Li + Adsorbent S 1 Add 150 mL of 0.3 mol / L nitric acid, soak for 60 min under stirring, filter, and obtain lithium-containing desorption solution L2 , determine its Li + Mg 2+ The content of filter cake S 2 That is, the perovskite type lithium adsorbent is reused, and the perovskite type lithium adsorbent can be recycled.
[0080] Embodiment 17
[0081] The difference from Example 1 is that 1000 mL of brine with the composition shown in Table 1 was taken, the pH was adjusted to 8.0 with 0.1 mol / L NaOH solution, 1.2 g of the prepared hydrogen-type adsorbent was added, and the mixture was stirred and soaked for 50 min, and filtered to obtain the adsorption mother solution L 1 , determine its Li + Mg 2+ Content, get filter cake S 1 That is the load Li + Adsorbent; when loaded with Li + Adsorbent S 1 Add 150 mL of 0.8 mol / L formic acid, soak for 60 min under stirring, filter, and obtain lithium-containing desorption solution L 2 , determine its Li + Mg 2+ The content of filter cake S 2 That is, the perovskite type lithium adsorbent is reused, and the perovskite type lithium adsorbent can be recycled.
[0082] Comparative Example 1
[0083] Example 1 of Chinese application CN116199256A.
[0084] Comparative Example 2
[0085] The difference from Example 1 is that in step S3, polyvinyl chloride, N-methylpyrrolidone, Li 0.29 La 0.57 TiO 3 The powders were mixed in a mass ratio of 2:8:3 to obtain a uniform mixture. The liquid droplets were added into deionized water by atomization method. Solid particles were formed through a phase separation process (about 1 h). The solid particles were taken out and dried at 60° C. to obtain a granulated lithium adsorbent.
[0086] The lithium adsorption capacity, lithium adsorption capacity retention rate after 5 cycles, and magnesium-lithium ratio in the desorption solution of the above examples and comparative examples are shown in Table 2. The lithium adsorption capacity bar graphs of Examples 1 to 3 are shown in Table 2. Figure 1 The bar graph of lithium adsorption capacity retention rate after 5 cycles is shown in Figure 2 , the magnesium-lithium ratio in the desorption solution is Figure 3 .
[0087] Test method:
[0088] Ion content: measured by ICP-OES instrument.
[0089] Lithium adsorption capacity = lithium ion content in the analytical solution × analytical solution volume ÷ adsorbent mass.
[0090] Forming effect: visual observation method, after the forming step, the lithium adsorbent still remains in a powder state, and those that are difficult to form are "none"; the lithium adsorbent can present a certain shape, but is fragile when moved, which is "poor"; the lithium adsorbent can maintain its basic shape when moved or under normal pressure, which is "medium"; the lithium adsorbent can maintain its shape intact and not fragile under greater pressure, which is "excellent".
[0091] Table 1
[0092]
[0093]
[0094] Table 2
[0095]
[0096] Depend on Figure 1 It can be seen that the lithium adsorbents in Examples 1 and 3 have relatively few adsorption sites and relatively low adsorption capacities; the lithium adsorbent in Example 2 has relatively more adsorption sites and relatively high adsorption capacity. Figure 2 It can be seen that the lithium adsorbents of Example 1, Example 2, and Example 3 still have a high adsorption capacity retention rate after being recycled for multiple times. Figure 3 It can be seen that the adsorption capacity of the lithium adsorbents of Examples 1 and 3 is relatively small, but the selectivity is slightly higher than that of Example 2; the adsorption capacity of Example 2 is larger, but the selectivity is correspondingly reduced.
[0097] The material of Comparative Example 1 is a titanium-based ion sieve, and powder is used for adsorption testing. However, the actual lithium extraction process requires further molding for easy operation, and the adsorption capacity of the titanium-based ion sieve will be significantly reduced after composite molding. The material of the present application has been molded in one step through a high-temperature reaction, and has advantages in lithium adsorption capacity in practical applications. Comparative Example 2 adopts granulation molding, and the adsorption capacity of the lithium adsorbent is significantly reduced after composite molding. Compared with the comparative example, the lithium adsorbents of each embodiment of the present invention have significant advantages in lithium adsorption capacity and the purity of lithium in the analytical solution while maintaining formability.
[0098] As can be seen from the above, each embodiment of the present invention synthesizes Li by sol-gel method combined with high temperature sintering x La y TiO 3 Precursor, and then acid elution to remove lithium to obtain perovskite lithium adsorbent Hx La y TiO 3 The lithium adsorbent is formed by high-temperature sintering, which avoids the loss of adsorbent capacity caused by traditional granulation. The adsorbent has stable properties, low acid leaching loss, long cycle life, and high lithium adsorption capacity and lithium selectivity. It is suitable for lithium extraction from a variety of salt lake brines by adsorption. In addition, it can be seen that when all process parameters are within the preferred range of the present invention, the comprehensive performance of the lithium adsorbent is the best.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a perovskite-type lithium adsorbent, characterized in that: The chemical formula of the perovskite lithium adsorbent is H x La y TiO3, x is 0.05-1.85, y is 0.05-0.65, and x+3y=2 is satisfied; the preparation method comprises the following steps: Step S1, mixing a lithium source, a lanthanum source, a titanium source and a complexing agent, and sequentially heating and drying to obtain a precursor gel; Step S2, oxidizing and sintering the precursor gel to obtain a precursor oxide; Step S3, forming and sintering the precursor oxide to obtain Li x La y TiO3 molding materials; Step S4, the Li x La y Acid leaching of the TiO3 molding material to obtain the perovskite-type lithium adsorbent; Wherein, the temperature of the oxidation sintering is 500-1200°C, and the temperature of the molding sintering is 950-1350°C.
2. The preparation method according to claim 1, characterized in that: In the step S2, The oxidation sintering includes a first sintering and a second sintering performed sequentially, wherein the temperature of the second sintering is higher than that of the first sintering, and the temperature difference is 450-550°C.
3. The preparation method according to claim 2, characterized in that: In the step S2, The temperature of the first sintering is 500-700° C., and the time is 3-5 hours; the temperature of the second sintering is 1000-1200° C., and the time is 18-22 hours.
4. The preparation method according to claim 1 or 2, characterized in that: In the step S3, The molding sintering includes a third sintering and a fourth sintering performed sequentially, and the temperature of the fourth sintering is higher than that of the third sintering, and the temperature difference is 200-250°C.
5. The preparation method according to claim 4, characterized in that: In the step S3, The third sintering temperature is 950-1150° C., and the time is 3-5 hours; the fourth sintering temperature is 1150-1350° C., and the time is 6-10 hours.
6. The preparation method according to claim 1 or 2, characterized in that: The heating rates of the oxidation sintering and the molding sintering are independently 0.2-8°C / min.
7. The preparation method according to claim 1 or 2, characterized in that: Before the forming and sintering, the step S3 further includes the step of ball milling the precursor oxide, the rotation speed of the ball milling is 450-550 rpm, and the time is 10-14 hours.
8. The preparation method according to claim 1 or 2, characterized in that: In the step S1, The molar ratio of the lithium source, the lanthanum source and the titanium source is (5-200):(5-65):100; and / or the molar ratio of the titanium source and the complexing agent is 1:(20-150).
9. The preparation method according to claim 1 or 2, characterized in that: In the step S1, The lithium source includes one or more of lithium nitrate, lithium carbonate and lithium chloride; and / or the lanthanum source includes one or more of lanthanum nitrate, lanthanum trioxide and lanthanum trichloride; and / or the titanium source includes one or more of titanium tert-butoxide, tetrabutyl titanate and titanium dioxide; and / or the complexing agent includes one or more of citric acid, fruit acid and citric acid; and / or The heating temperature is 60-120°C, and the drying temperature is 130-180°C.
10. The preparation method according to claim 1 or 2, characterized in that: In the step S4, The molar concentration of the acid used in the acid leaching is 0.5 to 1.5 mol / L, and the time of the acid leaching is 25 to 35 min; The acid includes an inorganic acid and / or an organic acid; the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid.
11. A perovskite lithium adsorbent, characterized in that: Obtained by the preparation method according to any one of claims 1 to 10.
12. A method for extracting lithium, characterized in that: The perovskite-type lithium adsorbent according to claim 11 is used as an adsorbent for lithium extraction.
13. The lithium extraction method according to claim 12, characterized in that: The lithium extraction method comprises the following steps: Take brine, add the perovskite lithium adsorbent for first soaking, filter, and obtain adsorption mother solution and loaded Li + Adsorbent; Take the load Li + The adsorbent is soaked in acid for a second time, filtered, and a lithium-containing desorption solution and a reused perovskite-type lithium adsorbent are obtained.
14. The lithium extraction method according to claim 13, characterized in that: The mass concentration of ions in the brine is: Na + 10~100g / L, K + 2~50g / L, Mg 2+ 0.1~50g / L, Ca 2+ 0.1~2g / L, Li + 0.01~1g / L, B 3+ 0.01~1g / L, SO4 2- 1~10g / L, Cl - 20-200 g / L, the mass ratio of Mg to Li is (0.1-5000):1; and / or The liquid-to-solid ratio of the brine to the perovskite-type lithium adsorbent is 1000mL:(0.8-1.2g); and / or the time for the first immersion and the second immersion is 50-70min; and / or the molar concentration of the acid is 0.3-0.8mol / L, and the acid includes an inorganic acid and / or an organic acid, and the inorganic acid includes one or more of hydrochloric acid, sulfuric acid and nitric acid; and / or the organic acid includes one or more of formic acid, acetic acid and citric acid.
Citation Information
Patent Citations
Preparation method of titanium lithium adsorbent precursor with high adsorption capacity
CN116199256A
Perovskite catalyst capable of removing nitrogen oxides and soot in diesel exhaust simultaneously and its preparation method and use
CN102626632A
Ferrous acid lanthanum / lithium nanometer compound powder photocatalyst and its preparing process
CN1631525A